Follow that bear if you dare! - Freedman, Claire; Edgson, Alison (Intercourse, PA : Good Books, 2008)
Hare and Rabbit bravely venture off on a bear hunt together, carefully following the instructions in Hare's "Best Book of Bear Hunting."
Originally published in 2007 in London, England by Little Tiger Press.
Keywords: Hares; Rabbits; Bears; Hares; Rabbits; Bears